Combination therapy in advanced urothelial cancer: the role of PARP, HER-2 and mTOR inhibitors. Issue 9 (1st September 2020) - Mollica, Veronica; Maggio, Ilaria; Lopez-Beltran, Antonio; Montironi, Rodolfo; Cimadamore, Alessia; Cheng, Liang; Rizzo, Alessandro; Giunchi, Francesca; Schiavina, Riccardo; Fiorentino, Michelangelo; Brunocilla, Eugenio; Massari, Francesco
ABSTRACT: Introduction: Despite significant advances in the treatment of metastatic urothelial carcinoma, including the advent of immune checkpoint inhibitors, this disease is still challenging to treat and associated poor outcomes remain. Genomic characterization of advanced-stage urothelial carcinoma is widening the field of potential treatments due to the identification of novel biologic drivers. Areas covered: In this review, we explore the role of PARP, HER-2, and mTOR inhibitors in the therapeutic scenario of advanced urothelial carcinoma, as these pathways are frequently altered in urothelial carcinoma. We report ongoing clinical trials involving these agents, either in monotherapy or in combination with other compounds, highlighting the dynamic scenario of metastatic urothelial carcinoma treatment. Expert opinion: Several challenges need to be faced in the development of new potential therapeutic strategies, such as inter/intratumoral heterogeneity and the lack of validated biomarkers.